Metabolic changes in elderly patients with major depression: evidence for increased accumulation of visceral fat at follow-up - Hamann-Weber, Bettina; Werner, Marc; Hentschel, Frank; Bindeballe, Nils; Lederbogen, Florian; Deuschle, Michael; Heuser, Isabella (Psychoneuroendocrinology, 2006)
The accumulation of visceral fat is promoted by a specific endocrine syndrome, which is similarly found in major depression. The aim of this study was to investigate whether visceral fat depots increase in depressed patients during a follow-up period explaining the increased risk for cardiovascular disorders. Intraabdominal fat was measured in 29 depressed patients and 17 controls by computer tomography at the level of lumbar vertebra 4. In patients fat measurements were done initially during a major depressive episode and again after a follow-up period of 14 months; in controls the mean time interval between measurements was 28 months. In both groups, saliva was taken at 800h over a period of seven days prior to each CT for the estimation of free cortisol. In patients only, an oral glucose tolerance test was also carried out. Compared to controls hyper- and normocortisolemic depressed patients showed a larger accumulation of visceral fat mass over time (hypercort.:132.0±45 vs. 144.7±47cm2, p=0.07; normocort.: 115.5±53 vs. 135.0±51cm2, p=0.002; controls: 130.1±66 vs. 137.3±76cm2, p=0.4), despite similar weight gain (hypercort.: 2.1±5kg, normocort.: 1.7±5kg and controls: 2.3±4kg). Further, normocortisolemic patients showed a trend for an higher percentile increase in visceral fat accumulation than controls (23.9±27 vs. 5.8±28%, p=0.07). At follow-up, free cortisol concentrations were still above normal in patients who had been hypercortisolemic at first assessment (35.0±8 vs. 28.8±18nmol/l, p=0.1). Fasting and 2h glucose concentrations were higher in hypercortisolemic compared to normocortisolemic patients at the index examination (6.2±1.1 vs. 5.0±0.05mmol/l, p=0.02; 11.5±2.7 vs. 7.8±1.9mmol/l, p=0.01). The larger proportion of visceral fat accumulation in patients may constitute a link for explaining the increased cardiovascular mortality in patients suffering from major depression.
Available online 6 October 2005
Gesehen am 20.10.2020